Begonia (Begoniaceae) from Batang Ai National Park and vicinity, Sarawak, Borneo, including six new species - Sang, Julia; Kiew, Ruth (Phytotaxa, 2016)
Nine Begonia species are recorded from the Batang Ai National Park and the forest area adjacent to the Park. Of these, six species are described here as new (Begonia acidulenta, Begonia bayae, Begonia compacta, Begonia edgariana, Begonia jenginensis and Begonia tebiang). All species belong to section Petermannia. A key to the new species and three species previously described by Lin et al. (2014) is provided. Following the guidelines for the IUCN Categories and Criteria, the proposed conservation status of the seven new species known from the national park is assessed as “Least Concern”.